A perspective from the National Eye Institute Extracellular Vesicle Workshop: Gaps, needs, and opportunities for studies of extracellular vesicles in vision research - Sun Young Lee; Mikael Klingeborn; Jeff W. M. Bulte; Daniel T. Chiu; Michael Chopp; Christopher W. Cutler; Saumya Das; Charles E. Egwuagu; Christie D. Fowler; Sarah F. Hamm‐Alvarez; Hakho Lee; Yutao Liu; et al. (Journal of Extracellular Vesicles)
Abstract With an evolving understanding and new discoveries in extracellular vesicle (EV) biology and their implications in health and disease, the significant diagnostic and therapeutic potential of EVs for vision research has gained recognition. In 2021, the National Eye Institute (NEI) unveiled its Strategic Plan titled ‘Vision for the Future (2021–2025),’ which listed EV research as a priority within the domain of Regenerative Medicine, a pivotal area outlined in the Plan. In alignment with this prioritization, NEI organized a workshop inviting twenty experts from within and beyond the visual system. The workshop aimed to review current knowledge in EV research and explore gaps, needs and opportunities for EV research in the eye, including EV biology and applications of EVs in diagnosis, therapy and prognosis within the visual system. This perspective encapsulates the workshop's deliberations, highlighting the current landscape and potential implications of EV research in advancing eye health and addressing visual diseases.